Development of a nutrition and physical activity booklet to engage seniors - Burke, Linda; Howat, Peter; Lee, Andy; Jancey, Jonine; Kerr, Deborah; Shilton, Trevor (BioMed Central Ltd, 2008)
Background: This paper describes the development and process evaluation of an interactive booklet aimed at motivating older adults to improve their nutrition and physical activity. Findings: The booklet was developed in consultation with seniors via focus groups, individual interviews and self administered questionnaires. The booklet was disseminated to a group of 114 seniors as the main component of a 12-week intervention program. Process evaluation was conducted during and at the end of the intervention period. A large proportion of participants (86%) were engaged in the program in that they had, as a minimum, read the booklet. The majority of the participants found the booklet provided them with useful and interesting advice in an easy-to-read and informative manner. Three quarters (76%) reported the materials to be motivating and increased their awareness of nutrition and physical activity, while 79% intended to continue with changes to their physical activity and diet after the program concluded.